Avanços e desafios ambientais da Educação Ambiental brasileira entre a Rio 92 e a Rio+20 - Otero, Patrícia Bastos Godoy (Universidade Federal de São Carlos, 2013)
The thesis discusses the progress and challenges in the field of environmental education (EE) in Brazil, in the period between the two world conferences on Environment and Development organized by the United Nations (UN) and performed in Brazil, the Rio-92 and Rio +20, which happened in 1992 and 2012 respectively. The main objective was to analyze the evolution of the Brazilian Environmental Education in the period between the two great conferences, from the systematization of information of official documents, reports published by the media about the two events and interviews with environmental leaders, politicians and technicians who were in the events and are prominent actors in the field of Environmental Education of Brazil. Since 1992 there has been the emergence and consolidation of various social practices and public policies that favored the development of environmental education in Brazil. Environmental education has influenced the thought and life of Brazilians.
Progress and challenges in the field of environmental educational (EE) in Brazil, in the period between the two conferences on Environment and Development organized by the United Nations (UN) and performed in Brazil, the Rio-92 and Rio+20
Keywords: Educação Ambiental; sustentabilidade; desenvolvimento sustentável; educação; meio ambiente - congressos; environmental education; sustainability; sustainable development; CIENCIAS BIOLOGICAS::ECOLOGIA